Propuesta de un péndulo electromagnético para la recolección de energía en usuarios de dispositivos de soporte de la marcha - Ramos Rosales, Verónica; González Landaeta, Rafael Eliécer (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
People with motor disabilities usually have slow movement patterns, which means that very little biomechanical energy can be harvested using wearable or portable sensors. In this work, an electromagnetic harvester is proposed to harvest energy during the gait of subjects using gait-support devices, in this case, a walker. The harvester consists of a simple pendulum where the suspended weight is formed by two neodymium permanent magnets. Three static coils connected in series have been arranged in such a way that their position coincides with the swinging movement of the suspended weight. So, when the pendulum is moved sideways from its resting, a gradient of the magnetic field is produced in each coil, generating an electromotive force. The performance of the proposed pendulum has been tested in bench conditions and in real conditions using a walker for the elderly. When the subject began or finished the gait with the walker, the pendulum moved sideways, making the magnets to move back and forth generating a peak-to-peak voltage of 2.2 V. This back-and-forth movement remains until the suspended weight reaches the equilibrium position due to the restoring force of the gravity. The generated voltage was not affected by the velocity of the gait, but by the beginning and ending of the gait. The proposed electromagnetic pendulum has demonstrated to be suitable to harvest energy from people with slow gait without attaching any sensor to the subject.